1998
DOI: 10.1016/s0741-5214(98)70002-3
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with endovascular aneurysm repair: Comparison of early results with outcome of conventional open repair

Abstract: Although less definitive than those for conventional operations, these early results suggest that endovascular AAA repair offers considerable benefits for appropriate patients. The results justify continued application of this method of AAA repair, particularly in the treatment of older persons at high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
157
1
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(174 citation statements)
references
References 47 publications
9
157
1
7
Order By: Relevance
“…Değişik çalışmalarda çok farklı oranlar da saptanmıştır. May ve ark.nın [22] çalışmasında %7, Brewster ve ark.nın [23] çalışmasında %21, Zarins ve ark.nın [24] çalışmasında %36, Beebe ve ark.nın [25] çalışmasında %5.6, Becquemin ve ark.nın [19] çalışmasında %27, Jordan ve ark.nın [18] çalışmasında %1.1 ve Lederle ve ark.nın. [16] çalışmasında ise %25 oranında bildirilmiştir.…”
Section: İstatistiksel Analizlerunclassified
“…Değişik çalışmalarda çok farklı oranlar da saptanmıştır. May ve ark.nın [22] çalışmasında %7, Brewster ve ark.nın [23] çalışmasında %21, Zarins ve ark.nın [24] çalışmasında %36, Beebe ve ark.nın [25] çalışmasında %5.6, Becquemin ve ark.nın [19] çalışmasında %27, Jordan ve ark.nın [18] çalışmasında %1.1 ve Lederle ve ark.nın. [16] çalışmasında ise %25 oranında bildirilmiştir.…”
Section: İstatistiksel Analizlerunclassified
“…Treatment of AEF usually consists of graft excision, closure of the duodenal defect, retroperitoneal debridement, and extra-anatomic bypass. Recently, stent-grafting has been utilized for the treatment of ruptured and nonruptured aortic aneurysms, traumatic aortic injuries, and various fi stulas involving the aorta [8][9][10][11][12]. This minimally invasive approach has the potential to overcome the problems encountered with standard open repair and is particularly attractive in highrisk patients and emergent situations.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, endovascular aneurysm repair (EVAR) was accepted as a compatible method to more conventional method from the viewpoint of its safety and favorable outcomes. [5][6][7] Earlier clinical studies on EVAR have reported significant decrease in intensive care unit (ICU) stay, hospital stay, major complications such as bleeding, and the 30-day mortality. Furthermore, due to its advantages including prompt recovery and early ambulation, EVAR had emerged as a substitute to surgery particularly for treating elderly patients with multiple comorbidities.…”
Section: Introductionmentioning
confidence: 99%